1997
DOI: 10.1017/s0031182097001534
|View full text |Cite
|
Sign up to set email alerts
|

Geographical genetic structure within the human lung fluke, Paragonimus westermani, detected from DNA sequences

Abstract: Nucleotide sequences were obtained for the second internal transcribed spacer of the ribosomal gene repeat and for part of the mitochondrial cytochrome c oxidase subunit I gene from geographical isolates of Paragonimus westermani from Japan, China, Korea, Taiwan, the Philippines, peninsular Malaysia and Thailand. Sequences were obtained from several other species of Paragonimus for comparative purposes. Two groups were recognized within P. westermani : an NE group (China, Japan, Korea, Taiwan) which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 9 publications
2
69
1
2
Order By: Relevance
“…However, it was possible to score relationships between some samples on the basis of their place of origin, in Group A and Group E we had isolates from Gwanda. The limited number of isolates in the present study and previous studies [28,29] perhaps missed the intraspecies phylogenetic structure. In Group D we have isolate 15 from Bulawayo and isolate 11 from Matopo which are not clustered, these isolates are completely separate from all the other isolates in the major cluster and this implies that they are substantially genetically different from the other isolates.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, it was possible to score relationships between some samples on the basis of their place of origin, in Group A and Group E we had isolates from Gwanda. The limited number of isolates in the present study and previous studies [28,29] perhaps missed the intraspecies phylogenetic structure. In Group D we have isolate 15 from Bulawayo and isolate 11 from Matopo which are not clustered, these isolates are completely separate from all the other isolates in the major cluster and this implies that they are substantially genetically different from the other isolates.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies [28,29] focusing on geographic comparisons showed low divergence among isolates. Our cluster analysis did not show a relationship among F. gigantica isolates and their geographical location.…”
Section: Discussionmentioning
confidence: 91%
“…Due to its conserved nature, the ITS2 region is a sensitive and reliable diagnostic marker at the species or genus level (Adlard et al 1993;Kane and Rollinson 1994;Blair et al 1997aBlair et al , 1997b. In comparison, the ITS1 region is far more variable and therefore useful for investigating intra-specific patterns of variation.…”
Section: Discussionmentioning
confidence: 99%
“…[8,7] To be more precise, the primers used were 3S (forward, 5'-GGTACCGGTGGATCACTCGGCTCGTG-3') [9] and A28 (reverse, 5'-GGGATCCTGGTTAGTTTCTTTTCCTCCGC-3'). [10] The PCR amplification was performed using 0.25 µm of each primer and 2.5 U of Taq polymerase (Invitrogen Corp., Carlsbad, CA, USA). The amplified products were extracted from agarose gels (Lonza, Rockland, ME, USA) and sequenced using the corresponding primers and the BigDye Terminator Cycle Sequencing kit (Applied Biosystems, Foster City, CA, USA) on an automated sequencer (ABI 310 Genetic Analyzer; Applied Biosystems).…”
Section: Morphological and Molecular Characterizationmentioning
confidence: 99%